Drug utilisation research in neonates: A step towards rational prescribing - AL-Turkait, Asma (2021)
Background: Since the initiation of drug utilisation research in the 1960s, the research in this area has continued to grow over the years, and in 2015 this search term reached over 20,000 hits in Medline. Whilst this area of research is known to be used in assessing the rational use of drugs, including prescribing, less is known about it in the neonatal population. In the UK, a drug utilisation study across neonatal units was conducted in 2009, but several limitations were observed that hinders a true representation of drug use patterns on a national level. Also, this study highlighted future research needs in one of the most challenging areas in neonatal medicine, which is managing patent ductus arteriosus (PDA). Ibuprofen is one of the drugs used to manage PDA; however, the rising reports of its adverse effects from observational studies requires further evaluation on when to use this agent, especially with the emergence of paracetamol as a suggestive alternative. In light of these existing gaps in knowledge, this thesis has been formulated to address a general question of ‘Where are we at when it comes to rational prescribing of drugs in one of the most vulnerable populations towards adverse effects from drugs?’. The aim was designed to assess the rational use of drugs in neonates at the very first step of the drug use process, which is prescribing. As a result, several questions were answered, and others set for future research.